Climate change vulnerability assessment for rare plants of the San Juan Region of Colorado - Grunau, Lee, author; Rondeau, Renée Jane, author; Kuhn, Bernadette, author; Handwerk, Jill, author; Colorado Natural Heritage Program, publisher (Colorado State University. Libraries, 2014)
The 5 million-acre San Juan Region lies in southwest Colorado and is considered part of the Four Corners area. The Colorado Natural Heritage Program tracks 122 plant species within this region. Recently published climate models for the Southern San Juan Region project a median decrease in May precipitation across southwestern Colorado and a 4.3° F increase in average annual temperatures, suggesting drought may become problematic for these species in the future (Lukas et al. 2014). As of 2014, we have conducted Climate Change Vulnerability Assessments using methodology developed by NatureServe for 60 of the tracked plant species known from the region, primarily focused on federally listed or agency sensitive species. Our results indicate that nearly 60% (36 species) of these plant species are extremely vulnerable to climate change. The most vulnerable species were from alpine, cliff and canyon, barrens, and groundwater dependent wetland habitats. Spruce-fir and ponderosa pine forests, and montane grasslands had the least amount of vulnerable species. Of the 60 species assesed, 37% (22 species) are endemic to the Four Corners region and most (19 species) are extremely vulnerable. Barrens support the highest number of endemic species of any habitat (7), and all but one barrens species is extremely vulnerable. We recommend developing climate adaptation strategies for extremely and highly vulnerable species and as time permits, assessing additional rare species.
Prepared for: Tres Rios Bureau of Land Management and San Juan U.S. Forest Service.
May 2014.
Keywords: sensitivity; exposure; San Juan Region; Colorado; climate change; rare plant species; NatureServe Climate Change Vulnerability Index